Implementation of Mobile Learning Design in the Flipped Direct Instruction Model to Increase Student Competency Using a Constructivist Approach - Irfan, Dedy; Lativa Mursyida; Akrimullah Mubai (Universitas Pendidikan Ganesha, 2023)
Mobile learning using technology is the main challenge for Generation Z students today. This challenge will affect students' independence and ability to learn. For this reason, this research aims to test the implementation of mobile learning using the Flipped Direct Instruction (FDI) model and develop Jarkom FDI learning media using a constructivist approach. This type of research is Quasi-Experimental Research. The control class and experimental class were used in this research. The Direct Instruction (DI) model is applied in the control class, and the FDI model is used for the experimental class. This research uses quantitative and primary data types. The methods used to collect data are questionnaires and tests. The instruments used to collect data were questionnaires and question sheets. The techniques used to analyze data are qualitative and quantitative statistical analysis. Data was obtained using test instruments and calculated using the Gain Score method. The results of the research are Jarkom FDI learning media along with mobile learning implementation data. This data obtains a percentage of the Gain Score, namely 75.04%, with a minimum percentage of 61.7% and a maximum percentage of 100.0%. 75.04% answered the research hypothesis that there is a significant influence of implementing mobile learning design in the FDI learning model with a constructivist approach on the results of computer network installation practicum learning. It was concluded that the learning model that uses mobile with a constructivist approach effectively improves students' cognitive and psychomotor abilities. The results of this study are expected to be one of the qualified options for increasing the effectiveness of the implementation of Computer Network Installation learning.